Guide to exercise and weight control Cedric X. Bryant - Bryant, Cedric X. (New York: Monterey Bay Video, 2002)
This program focus on the current issues regarding nutrition, exercise and weight control and also discusses many of the more popularly held weight-control myths and misconceptions.
Keywords: Exercise; Weight control